Association of birth order with cardiovascular disease risk factors in young adulthood: a study of one million Swedish men. - Aline Jelenkovic (Public Library of Science (PLoS), 2013)
Background Birth order has been suggested to be linked to several cardiovascular disease (CVD) risk factors, but the evidence is still inconsistent. We aim to determine the associations of birth order with body mass index (BMI), muscle strength and blood pressure. Further we will analyse whether these relationships are affected by family characteristics. Methods BMI, elbow flexion, hand grip and knee extension strength and systolic and diastolic blood pressure were measured at conscription examination in 1,065,710 Swedish young men born between 1951 and 1975. The data were analysed using linear multivariate and fixed effects regression models; the latter compare siblings and account for genetic and social factors shared by brothers. Results Fixed effect regression analysis showed that birth order was inversely associated with BMI: second and third born had 0.8% and 1.1% (p<0.001) lower BMI than first-born, respectively. The association pattern differed among muscle strengths. After adjustment for BMI, first-born presented lower elbow flexion and hand grip strength than second-born (-5.9 N and -3.8 N, respectively, p<0.001). Knee extension strength was inversely related to birth order though not always significantly. The association between birth order and blood pressure was not significant. Conclusions Birth order is negatively associated with BMI and knee extension strength, positively with elbow flexion and hand grip strength, and is not associated with blood pressure among young men. Although the effects are small, the link between birth order and some CVD risk factors is already detectable in young adulthood.